School Policy Analysis on the Impact of Gadget Use on Primary School Children - Desi Rahmawati; Muhammad Al Mighwar (Penerbit Hellow Pustaka, 2025)
The purpose of this study was to describe the results of an analysis of school policies regarding the impact of using gadgets on elementary school children. The media used is descriptive qualitative method, which is data collection in accordance with library research. The results of this study are that the impact of using gadgets on elementary school children is quite significant, the use of gadgets that are too long and without parental supervision has an impact on dependence and influences the development of behavior and social interaction, children tend to be difficult to get along with, easily angry and immersed in the world that they create with their gadgets. Therefore the importance of school policies regarding the use of gadgets in elementary schools regarding the prohibition of bringing and using gadgets at school. And to overcome the demands of the times regarding technology, online learning, and so that children are not clueless, schools have made a strategy by providing multimedia and wifi rooms for students to use and find learning information with guidance from the teacher during study hours. In addition, the school also regularly schedules teacher and student meetings as a means of education and evaluation of how students are at school so that they can minimize the impact of using gadgets and educational goals can be achieved.